Proceedings of the International Conference of Innovation in Media and Visual Design (IMDES 2020) 2020
DOI: 10.2991/assehr.k.201202.072
|View full text |Cite
|
Sign up to set email alerts
|

Visual Communication as A Medium Sending Standard Operating Procedure (Sop) Message to Public During Pandemic Covid-19

Abstract: This concept paper discusses the importance and capability, implementing visual communication in the Standard Operating Procedure (SOP). As the whole country faced with Covid-19, visual communications became widely used method delivering information. Social media usage was increasing in digital and online activities because of demand getting information for Covid-19. Visual communication helps identify instructions, guidance and actions that need to be done for Covid-19. A lot of information in the form of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The result of this study aligns with previous research conducted by Tahir et al (2020) and Delicado & Rowland (2021), which also emphasize that visual elements possess their own rhetoric, conveying specific meanings. However, due to the exceptional circumstances of the Covid-19 Pandemic, it is essential for the government to consider the habits of the community (Schirato & Webb, 2004) and promote the internalization of a healthy lifestyle within the population.…”
Section: Table 3 Communalitiessupporting
confidence: 90%
See 1 more Smart Citation
“…The result of this study aligns with previous research conducted by Tahir et al (2020) and Delicado & Rowland (2021), which also emphasize that visual elements possess their own rhetoric, conveying specific meanings. However, due to the exceptional circumstances of the Covid-19 Pandemic, it is essential for the government to consider the habits of the community (Schirato & Webb, 2004) and promote the internalization of a healthy lifestyle within the population.…”
Section: Table 3 Communalitiessupporting
confidence: 90%
“…Previous research conducted by Tahir et al (2020) in the context of Covid-19 explored how the Government of Malaysia disseminated guidelines and standard operating procedures to the public for controlling the spread of the virus and managing infected citizens. The study found that messages conveyed through visual communication elements were effective in reducing citizen panic amid the high rate of Covid-19 transmission in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A Cartoon During the Pandemic Process, from: 'Why should we stay 2m away from others when socially distancing?' by Dr. Cilein Kearns (Artibiotics) (Kearns ve Kearns, 2020, p. 140) Tahir et al (2020) indicate that although visual communication is used as an important element when submitting messages during COVID-19, the understanding and acceptance of the target audience before the visual presentation is also an important factor to be considered. Therefore, an image full of messages should be following the audience addressed through a suitable channel and platform.…”
Section: Metaphoric Visuals For the Covid-19 Pandemicmentioning
confidence: 99%
“…The official data released by the Malaysian national news agency, Bernama, helped the public to be aware of the SOPs that are in place. Tahir et al (2020) highlighted that it is important to use visual communication in communicating SOPs. Undeniably, visual communication has become a widely used method in producing messages of Covid-19 SOPs on mass media.…”
Section: Introductionmentioning
confidence: 99%